The building features acquired from the indigenous technology contributing in the better performance during earthquake: a case study of Bhaktapur City - Gautam, Dipendra (Journal of Science and Engineering, 2014)
This paper compiles the indigenous technologies adopted in the Bhaktapur municipality, Nepal in the unreinforced masonry construction of traditional Newari houses constituting more than 90% buildings in Bhaktapur municipality and their significance during the earthquake. The building units adopted in this area are studied with respect to their performance during earthquake on the basis of seismic resistant design philosophy. The traditionally built non-engineered buildings have drawn the attention of disaster managers for many years; in this regard, the unreinforced masonry buildings (Newari houses) were assessed after the Sikkim-Nepal boarder earthquake of 2011.Still, the buildings constructed before the starting of engineering construction in Nepal are widely used for residential purpose at this culturally rich city and the traditional building construction technology which is the indigenous technology has been practiced for centuries too. The building features are analyzed with respect to their seismic performance and their contribution was analyzed as per the historical database; established practices and theories for earthquake resistant design (EQRD). The collected features and the analyses proved the features of the buildings to be sound during earthquake, though; the buildings were constructed with indigenous technology which nevertheless consults the EQRD within it. The indigenous technology at this city has been attached with the culture of the Newars for centuries.